Polyvinyl Butyral/Graphene Oxide Composite Coating for Properties Improvement - Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology, 2023)
In this paper, polyvinyl butyral (PVB) composite coating was prepared with graphene oxide (GO) for improving mechanical properties, corrosion protection, thermal oxidation stability. Fourier-transform infrared spectroscopy (FT-IR), Thermogravimetric analysis (TGA), Field Emission Scanning Electron Microscopy (FESEM),... were used to examine the results. Presence of GO in composite coating was characterized by FT-IR. Corrosion protection of PVB coating containing GO was determined with salt mist testing with 4 cycles  in 5% NaCl, each cycle included 2 hours spraying at 35±2 o C , kept in humidity condition for 7 days at 40± 2 o C with relative humidity of 93 ± 2%. Effects of GO on adhesion, flexibility, impact resistance, relative hardness and thermal oxidation stability of PVB composite coatings were also investigated. Results showed that GO content in PVB composite coating of 1.5 wt.% had significantly enhanced mechanical properties, corrosion resistance of PVB composite coating. Thermal oxidation resistance of PVB composite coating with 1.5 wt.% of GO was much higher than that of PVB composite coating without GO.